2020
DOI: 10.1007/s00259-020-04880-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of [18F] JNJ-64326067, a novel candidate PET tracer for the detection of tau pathology in Alzheimer’s disease

Abstract: Purpose The accumulation of misfolded tau is a common feature of several neurodegenerative disorders, with Alzheimer’s disease (AD) being the most common. Earlier we identified JNJ-64326067, a novel isoquinoline derivative with high affinity and selectivity for tau aggregates from human AD brain. We report the dosimetry of [ 18 F] JNJ-64326067 and results of a proof-of-concept study comparing subjects with probable Alzheimer’s disease to age-matched healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…[ 18 F]-JNJ-067 is a new tau PET tracer with a demonstrated ability to differentiate between AD and HC participants. 47 The goal of this study was to evaluate the performance of [ 18 F]-JNJ-067 using a more diverse cohort of HC, MCI, AD, and PSP participants, and to explore different approaches to quantitation of data. Although there are a handful of tau tracers currently in use, researchers are still searching for an ideal tau tracer that fulfills all of the following: binds to its target with a high dynamic range; has no or minimal offtarget signal; reaches a steady state within a half-life; and has a high test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 F]-JNJ-067 is a new tau PET tracer with a demonstrated ability to differentiate between AD and HC participants. 47 The goal of this study was to evaluate the performance of [ 18 F]-JNJ-067 using a more diverse cohort of HC, MCI, AD, and PSP participants, and to explore different approaches to quantitation of data. Although there are a handful of tau tracers currently in use, researchers are still searching for an ideal tau tracer that fulfills all of the following: binds to its target with a high dynamic range; has no or minimal offtarget signal; reaches a steady state within a half-life; and has a high test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The initial study of [ 18 F]-JNJ-067 showed this tracer has a high affinity for aggregated tau (K i ¼ 2.4 nM), low offtarget binding to amyloid and MAO enzymes shown using autoradiography in human brain tissue, and favorable kinetics in mice and monkeys. 46 Subsequently a study by Schmidt et al 47 evaluated [ 18 F]-JNJ-067 PET data collected for three hours from 5 HC and 5 AD subjects. In that study, 1.5 hours of data acquisition produced distribution volume ratios that were highly correlated with DVRs obtained in 3 hours of scanning (r 2 ¼.99), with large effect sizes in distinguishing AD participants from controls.…”
Section: Introductionmentioning
confidence: 99%
“…Designers of these new generation tracers are focusing on improving in vivo characteristics such as higher selectivity, faster brain penetration/washout, and less off-target binding. Preliminary studies for these newer tracers have shown promising results (Declercq et al, 2017 ; Kuwabara et al, 2018 ; Guehl et al, 2019 ; Rombouts et al, 2019 ; Teng et al, 2019 ; Schmidt et al, 2020 ).…”
Section: Pet Tracers For Imaging Tau Tanglesmentioning
confidence: 99%
“…Observation of fMRI techniques will help detect dementia and change in neuron connections, determining the change in brain function. On the other hand, the level of amyloid deposition in certain parts of the brain, which can be seen by amyloid PET biomarker, will help to survey AD severity for patients [5]. However, especially in cases of dementia diagnosis, mentioned biomarkers could not help accurately identify or predict cognitive deterioration due to individual threshold differences in each subject [6].…”
Section: Introductionmentioning
confidence: 99%